(untitled) (CIPEEX, 2025)
The study in question explores the relationship betweencollagen supplementation and skin health, addressingseveral aspects of the topic. The skin, the largest organ of the human body, performs essential functions such as protection, temperature regulation, and sensory perception. Composed of the epidermis, dermis, and hypodermis, the skin is crucial for immune response and intercellularcommunication. However, with aging, the skin undergoeschanges such as wrinkles, loss of elasticity, and dryness, due to genetic and environmental factors, as well as decreased cellular turnover.Nutrition, particularly the intake of vitamins, minerals, and proteins, directly impacts skin health. Proteins are essential for the synthesis of collagen and elastin, and theirdeficiency can impair skin elasticity and healing. Collagenand protein supplements have shown potential to improveskin elasticity and reduce wrinkles, although effects varydepending on composition and dosage.The study aims to evaluate the efficacy of Peptechcollagen supplementation at two daily doses (2.5 g and 10 g) in improving skin appearance, reducing expressionlines, and modulating plasma levels of TGF-beta and VEGF. It will recruit 100 women aged 35 to 58, dividedinto supplementation groups and monitored over threemonths. Evaluations will include measures of hydration, oiliness, flexibility, and levels of the aforementionedbiomarkers.The ultimate goal is to validate the effects of Peptechcollagen and generate scientific data to support industryclaims, potentially expanding the market for this supplement. The study aims to result in a scientificpublication demonstrating the effectiveness of collagen in improving skin quality.